Heterosis and genetic diversity analyses involving tropical and temperate popcorn populations - Risso, Leonardo Alves (2019)
Understanding the heterosis and genetic diversity is crucial to choose potential popcorn (Zea mays L. ssp. mays) populations to be used in future hybrid programs. The objective of this study was to analyze heterosis and genetic diversity between tropical and temperate popcorn populations. Nine popcorn populations from different origins were crossed by diallel design and genotyped using 23 microsatelite markers. The parental populations, selfed populations, the hybrids and reciprocals were evaluated in 2017/18 growing season for expansion volume and grain yield at two locations in Minas Gerais, Brazil. The heterosis analysis were performed according to the analysis II of Gardner and Eberhart and fitted to the unrestricted model. The genetic diversity analysis was assessed by the complement of Jaccard similarity. There were genetic variability and dominance for expansion volume and grain yield. The cluster analysis based on microsatelite markers grouped nine popcorn populations into two groups. The grouping with hierarchical and Tocher’s procedures were in accordance with the origins. The genetic distance was weakly correlated with heterosis for grain yield. Regarding expansion volume, there was no significant correlation. The midparent heterosis was used to assign the nine populations into heterotic groups, since that correlation was irrelevant between genetic distance and heterosis. The Tocher’s optimization procedure established four heterotic groups, and a promising combination (Sintético-UFV × UFV-MP5) was identified.